Cross-browser compatibility : Problem and solution / Junaidah Ab Aziz - Ab Aziz, Junaidah (Faculty of Computer and Mathematical Sciences, 2004)
In the Internet, multitude of badly conceived and poorly designed sites is now populating the web. The emergence of various browsers also makes cross-browser compatibility more difficult to achieve. In achieving this compatibility, web designers are burden with many problems from Hypertext Mark-up Language (HTML) errors to client-side scripting such as JavaScript to additional plug-ins to even the browsers own bugs. Therefore in this research, the MyFTMSK website have to be tested to see how the pages will be visibly rendered for any particular user using various browsers such as Internet Explorer 6.0, Internet Explorer 5.0, Opera 7.22, Opera 6.0, Mozilla 1.7, Mozilla 1.6, Netscape Navigator 7.22 and Netscape Navigator 4.8 and the effect of 1024x768 and 800x600 pixels resolution. The possible solutions to improve these accessibility problems were generated by using trial and error debugging or validators program and then were applied to MyFTMSK website. The result shows Opera 7.22 is the most compatible browser to be use with this website and 1024x768 pixels resolution is the most suitable resolution. In conclusion, each browser has its built in engine of parsing documents, and not all browsers have the same way of translating web documents. Therefore incompatibilities in terms of browser functions carmot be resolved until browser developers find a standard way of translating web documents.